Application of international Human Rights instruments (IHRIs) by domestic courts : a comparative study of Rwanda and Ghana - Quashigah, Edward Kofi (University of Pretoria, 2012)
Thesis (LLM (Human Rights and Democratisation in Africa)) -- University of Pretoria, 2011.